House Buyers Preferences Among Young Urbanites in Malaysia - Mohd Zairul (MAJ - Malaysia Architectural Journal, 2019)
Housing preferences are basically correlated with the status of one’s financial economy. The increase in housing demands due to change of lifestyle has increased recently. However, current research only focusing on small samples in Kuala Lumpur city area. Therefore, this paper reports the trend of house buyers among young urbanites in several big cities in Malaysia including Selangor, Kuala Lumpur, Penang and Johor Bahru among 400 respondents. All the data gathered are analyzed using Statistical Package for The Social Sciences (SPSS), Version 22 For Windows and for each research question are discussed in the discussion parts consisted of descriptive statistics. Findings identified proximity to public transportation is the highest preferences in the new housing thus suggesting a more ‘transit- oriented development’ friendly in the new development in the future. This research will benefit housing developers and extend the existing framework on housing preferences in Malaysia.